Regulatory interactions among autologous T cell clones. Human bifunctional T cell clones regulate the activity of an autologous T cell clone. - Naor, D; Essery, G; Tarcic, N; Kahan, M; Feldmann, M (1991)
In contrast to the ease of cloning and characterizing, at the molecular level, helper and cytotoxic T cells, suppressor T cells remain an enigma, and their existence as discrete entities is being increasingly challenged. Here we review evidence that CD4+ regulatory clones, capable of expressing both helper and suppressor functions, may account for much of the suppressor function. It is suggested that a single T cell clone, depending on the signals it receives from its environment, may release either helper or suppressor cytokines. Studying such clones under defined conditions (providing suppressor signals), may preclude detection of their helper capacity. Since some therapeutic approaches in various human diseases are based on the manipulation of helper and suppressor functions, the question whether committed suppressor cells exist has important practical implications in medicine.